Nature-Based Guided Imagery as an Intervention for State Anxiety - Nguyen, Jessica; Brymer, Eric (Frontiers in Psychology, 2018)
Anxiety is a significant mental health issue in modern society and empirical research into effective interventions to address anxiety has been extensive. Spending time in nature is one approach that has demonstrated anxiolytic effects. However, in some situations and contexts spending time in nature in order to reduce anxiety symptoms may not be possible. For example, in therapeutic settings delivered in a space with no access or exposure to any nature stimuli in the immediate surrounding environment. Guided imagery has also proven to be effective for reducing anxiety symptoms. Thus, nature-based guided imagery might help to overcome the limitation of access to nature and strengthen the impact of guided imagery interventions. The current study investigated the effectiveness of nature-based guided imagery (GI) on anxiety reduction. Participants (n=48, 18 males, 30 females, Mage = 34.54, SDage = 12.91, age range = 19 – 71 years) with moderate levels of either trait or state anxiety as measured by the state-trait anxiety inventory (STAI) were recruited. Participants undertook both a nature-based GI session and a traditional non-nature-based GI session and their pre- and post- state anxiety levels were measured in each GI session. It was anticipated that post state anxiety scores would be significantly lower for both GI conditions and that a significantly greater anxiety reduction would be found in the nature-based GI than the urban-based GI. A two-way analysis of variance for repeated measures revealed results that supported both hypotheses. This study was the first to compare a nature based GI intervention with a traditional (non-nature based) GI intervention. Findings indicate that nature-based GI interventions are highly effective anxiety management interventions that have the added benefit of being cost-effective and easily accessible.